2019
DOI: 10.21451/1984-3143-ar2018-0149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metronidazole on placental and fetal development in albino rats

Abstract: Metronidazole is an antiprotozoal and antibacterial used in gynecology and obstetrics for the treatment of parasitic infections. However, despite having clinical use for more than three decades, questions about the safety of its use during pregnancy is not well understood. Thus, the present study evaluated the effect of metronidazole on placental and fetal development in pregnant rats. Metronidazole was orally administered by gavage at a dosage of 130 mg/kg for 7 and 14 days. Morphological analysis, morphometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In female rats, the process of implantation of the blastocyst in the endometrium occurs from the 1st to the 5th day of gestation and, during this period, the embryo is quite susceptible to lethality [ 40 ]. The success of pregnancy depends on the maintenance of progesterone and estrogen levels.…”
Section: Discussionmentioning
confidence: 99%
“…In female rats, the process of implantation of the blastocyst in the endometrium occurs from the 1st to the 5th day of gestation and, during this period, the embryo is quite susceptible to lethality [ 40 ]. The success of pregnancy depends on the maintenance of progesterone and estrogen levels.…”
Section: Discussionmentioning
confidence: 99%
“…The last research article in this Special Issue, reported by Abdrabou et al ( contributor 9 ), showed that treatment with metronidazole, an antiprotozoal and antibacterial agent, during pregnancy induced teratogenicity and hepatoxicity and other fetal defects. Thus, metronidazole should be avoided during pregnancy, as another study showed the teratogenic effects with this compound in an animal model [ 10 ].…”
Section: An Overview Of Published Articlesmentioning
confidence: 99%
“…Females are among the most vulnerable to being infected with vaginitis caused by parasites or pathologies related to childbirth and the care of women giving birth [1]. Intentionally or unintentionally, women rely broadly on medication or pharmaceutical therapy to treat protozoal and/or bacterial infections during pregnancy or when not pregnant [2].…”
Section: Introductionmentioning
confidence: 99%